Psoriasis: A Case Report - Liyenka Belusi Tantra; Nathalia Gabriella; Stephanie Astrid Gunawan; Nabilla Aisya Zhavira; Theresia Monica Rahardjo; Epi Panjaitan; Peter Nugraha Soekmadji (Medical Clinical Update, 2022)
Background Psoriasis is a chronic inflammatory skin disease with a strong genetic predisposition and autoimmune pathogenic traits. Psoriasis vulgaris is also called plaque-type psoriasis, and is the most prevalent type. Psoriasis vulgaris is chronic inflammatory disease and characterized by periods of attack and remission. The chronicity of psoriasis vulgaris can affect patient’s quality of life. Case presentation A 33-year-old male came to Unggul Karsa Medika Hospital’s outpatient department with itchy, scaly, red plaques all over his body except his palms, soles, and face. The patient went to the dermatologist because his symptoms were getting worse and worse. Dermatologic examination concludes the lesions as multiple, generalized, discrete, circumscriptive, elevated, dry, regular-discoid erythematous plaques with psoriasiform scales located at the patient’s head, ears, nape, back, chest, belly, both arms and legs. Conclusion The diagnosis of psoriasis vulgaris was made based on history and clinical symptoms, supported by histopathological results. Treatment optimization and transitioning for moderate-to-severe plaque psoriasis include methotrexate or cyclosporine, along with topical therapy and supportive therapy.